CLINICAL PHARMACOLOGY OF HYPOLIPIDEMIC DRUGS - Rasulov Boburjon Abduqahhorovich, (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2025)
This article explores the clinical pharmacology of hypolipidemic (lipid lowering) drugs, which play a pivotal role in the prevention and treatment of atherosclerotic cardiovascular disease. It outlines the pharmacodynamics, pharmacokinetics, classification, indications, and safety profiles of major hypolipidemic agents, including statins, fibrates, bile acid sequestrants, cholesterol absorption inhibitors, PCSK9 inhibitors, and emerging therapies. The article highlights their mechanisms of action, therapeutic applications, and considerations for personalized lipid management.